2021
DOI: 10.3390/jcm10112375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Air Pollution on Lung Function among Preadolescent Children in Two Cities in Poland

Abstract: Ambient air pollution impairs lung development in children, particularly in industrialized areas. The air quality in Zabrze, a city located in the Upper Silesian Industrial Region of Poland, is among the worst in Europe. We compared lung function and the frequency of respiratory or allergic symptoms between children living in Zabrze and those living in Gdynia, a city on the Baltic coast, which has the best long-term air quality in Poland. We enrolled children aged 9–15 years from both cities who were able to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In China, high concentrations of coarse PM (10–2.5) were a strong predictor of district-specific prevalence for respiratory health problems including wheezing and cough [ 84 ]. Children with long-term exposure to air pollutants in industrial Polish cities also had impaired lung development and reduced lung function compared with children from cleaner areas [ 13 ]. All the above findings coupled with our results reinforce that the effects of long-term exposures need to be better understood, particularly the association between exposures and different outcome variables such as ARIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, high concentrations of coarse PM (10–2.5) were a strong predictor of district-specific prevalence for respiratory health problems including wheezing and cough [ 84 ]. Children with long-term exposure to air pollutants in industrial Polish cities also had impaired lung development and reduced lung function compared with children from cleaner areas [ 13 ]. All the above findings coupled with our results reinforce that the effects of long-term exposures need to be better understood, particularly the association between exposures and different outcome variables such as ARIs.…”
Section: Discussionmentioning
confidence: 99%
“…PM penetrates not only the lungs’ gas exchange region, but can further penetrate into the circulatory system [ 12 ]. PM exposure is associated with airway inflammation, decline in lung function [ 13 ], incidence and exacerbation of asthma and COPD, and increased susceptibility to infections [ 12 ]. Upon deposition on the surface of pulmonary bronchioli and alveoli, PM is internalized into epithelial cells and macrophages and disrupts lung function by triggering a series of processes, including apoptosis and autophagy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we tested a home spirometer with the ability to automatically transfer results in real-time to a doctor's panel. We opted for the AioCare system because it had been tested at home on large groups of patients with other lung diseases, such as asthma [22,23], and as a screening tool for early detection of chronic obstructive pulmonary disease in primary care in both adult [24] and pediatric populations [25].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that compared to a group of children aged 9–15 living in Gdynia, a city located on the Baltic coast, adolescents living in Zabrze had significantly worse spirometry outcomes [ 50 ]. The difference was observed for forced vital capacity (FVC) and forced expiratory volume in one second of expiration (FEV1) [ 50 ].…”
Section: Childrenmentioning
confidence: 99%
“…Moreover, a positive relationship between the prevalence of bronchitis and bronchiolitis and the combined effect of a rise in PM and SO 2 concentrations was observed in Chorzów [ 59 ]. For children living in Zabrze, an increased prevalence of seasonal rhinorrhoea and cough episodes was observed [ 50 ]. Brożek et al observed that an improvement of ambient air quality, also in Chorzów, correlated with a decreasing prevalence of cough [ 60 ].…”
Section: Childrenmentioning
confidence: 99%